Chemical and lead isotope constraints on sources of metal pollution in street sediment and lichens in southwest Ohio - LeGalley, Erin; Widom, Elisabeth; Krekeler, Mark P.S.; Kuentz, David C. (Applied geochemistry, 2013)
► Urban pollution study in a neighborhood adjacent to a coal-fired power plant. ► Pb isotopic compositions determined in street sediment and lichen samples. ► Geochemistry is consistent with Pb contamination from yellow road paint containing PbCrO4. Lead isotopic compositions were determined in street sediment and lichen samples to constrain the sources of metal pollution near a coal-fired power plant in SW Ohio. Previous studies of the street sediment found elevated levels of Cr, Cu and Ni, and extremely high levels of Pb and Zn. Although initial investigations suggested the presence of coal-derived pollution, Pb isotopes were employed to investigate the importance of additional sources. Highly variable concentrations of Pb in sieved (<38μm) street sediment and lichen samples range from 130 to 1399ppm and 11 to 53ppm, respectively. Street sediment and lichen samples exhibit a strong positive correlation of 208Pb/204Pb vs. 206Pb/204Pb, 208Pb/206Pb vs. 207Pb/206Pb, 207Pb/206Pb vs. 206Pb/204Pb, and 207Pb/204Pb vs. 206Pb/204Pb consistent with Pb contamination from road paint containing PbCrO4 as a yellow pigment. Extremely high concentrations of Pb in road paint samples (812–6305ppm) suggest road paint containing PbCrO4 is a major contributor to Pb levels in urban environments. Additional sources fro Zn and Cu beyond pollution derived from coal and road paint are proposed. Fine particulates containing potentially harmful metals in street sediment may be re-suspended in the air, as suggested by their presence in lichens, and pose a respiratory risk to human health. These metals may pose a risk to the greater environment, such as aquatic ecosystems subject to stormwater discharge from urban areas. This study is relevant and applicable to other urban settings, and prevention and remediation strategies for contaminated street sediment are recommended.